Strategies for Mitigating Compromise in the Conduct of Senior School Certificate Examinations in Edo State, Nigeria - Osaretin, Osadolor (Advances in Social Sciences Research Journal, 2016)
For more than two decades now, the challenges of examination malpractice in Nigerian secondary schools has remained unresolved; in spite of several efforts put up by the federal government to stop the menace. It is contended that compromise in the exercise should be responsible for the continued prevalence of the practice. To address the issue, four research questions were raised. The third research question was however formulated into hypothesis. The descriptive survey design was used to collect data from the 291 supervisors out of the 582 non first timer supervisors who participated in the supervision of the 2016 WAEC conducted SSCE in Edo State. The study revealed that the examination centres were the main point of compromise. Seven strategies were suggested for adoption towards mitigating the act of compromise in the exercise.